Cutaneous sarcoidosis with protean manifestations: a rare case report - Pravin, Avinash; Srinivasan, Shreya; Thomas, Jayakar (International Journal of Research in Dermatology, 2019)
Sarcoidosis is a multisystem granulomatous disease of unknown origin. The lung is the most commonly affected organ, but skin is frequently involved. Skin involvement is important because it may be the presenting sign of systemic sarcoidosis. Here, we report a rare case of sarcoidosis with systemic manifestations, in a 39 year old male patient.